2010
DOI: 10.1002/dvdy.22345
|View full text |Cite
|
Sign up to set email alerts
|

Serum and glucocorticoid‐inducible kinase 1 (SGK1) is necessary for vascular remodeling during angiogenesis

Abstract: The unquestionable importance of the cardiovascular system for pre-and postnatal life has prompted dissection of the molecular mechanisms underlying its development. Serum and glucocorticoid-inducible kinase 1 (SGK1) is a serine/threonine kinase lying downstream of the phosphoinositide 3 (PI3) kinase pathway, whose embryonic function remains unknown. Here, we show that disruption of Sgk1 in the mouse C57BL/6J genetic background leads to embryonic lethality at embryonic day 10.5-11.5 due to severe embryonic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 62 publications
1
39
0
Order By: Relevance
“…In this study, we demonstrated that a high‐fat diet increased both SGK1 abundance and Ser‐422 phosphorylation in the vasculature of DIO mice. Previous studies from our laboratory and others demonstrate that enhanced expression or activation of SGK1 exacerbate cellular processes that lead to pathological vascular remodeling . Thus, our findings suggest that SGK1 is activated in the vasculature with the onset of obesity and may participate in cellular processes that lead to vascular dysfunction.…”
Section: Discussionsupporting
confidence: 65%
“…In this study, we demonstrated that a high‐fat diet increased both SGK1 abundance and Ser‐422 phosphorylation in the vasculature of DIO mice. Previous studies from our laboratory and others demonstrate that enhanced expression or activation of SGK1 exacerbate cellular processes that lead to pathological vascular remodeling . Thus, our findings suggest that SGK1 is activated in the vasculature with the onset of obesity and may participate in cellular processes that lead to vascular dysfunction.…”
Section: Discussionsupporting
confidence: 65%
“…SGK1 is up-regulated by ischemia [53,54] and may participate in the stimulation of tumor vascularization [55]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our laboratory demonstrated for the first time that genetic disruption of SGK1, which is activated in the myocardium by mIGF-1 overexpression (in parallel with PDK1 and JNK1), reduces the expression of Notch signaling genes in mouse embryos, impairing heart structure and function (Catela et al, 2010).…”
Section: Migf-1 Enhances Sirt1 Expression In Cardiomyocytes Through Jmentioning
confidence: 99%